Bariatric surgery in a public hospital: a 10‐year experience. Issue 9 (23rd May 2022) - Aly, Ahmad; Spiro, Calista; Liu, David S.; Mori, Krinal; Lim, Hou K.; Blackham, Ruth; Erese, Raymund J.
Abstract: Introduction: Obesity is common and adversely impacts quality‐of‐life and healthcare cost. In Australia, less than 10% of bariatric surgeries are performed in the public sector. This study reports our 10‐year experience from a high volume public bariatric service which delivers multi‐disciplinary care for primary and revisional procedures with mid‐ to long‐term follow‐up. Methods: A prospectively maintained database of all patients who underwent bariatric surgery from January 2010 to January 2020 at a tertiary metropolitan hospital was analysed. We analysed patient demographics, comorbidities, perioperative outcomes, 2‐ and 5‐year weight loss as well as comorbidities reduction. Results: A total of 995 patients underwent 1086 (674 primary and 412 revisional) bariatric procedures with mean age of 46.9 years, mean BMI of 49.6 ± 9.1 kg/m 2 and 92% patients with ≥1 obesity‐related co‐morbidity. Length‐of‐stay was longer for revisional than primary surgery (5.6 vs. 3.5 days). Major complication rate was 4.2%. Overall, % Total body weight loss (%TBWL) for primary surgeries at 2 years was 26.2%, and for revision surgery was 17.4%. At 2 years follow‐up, treatment was ceased or reduced in 65% of diabetics, 29% of hypertensive patients and 69% of sleep apnoea patients. Conclusion: This study confirms that bariatric surgery in Australia can be delivered effectively in resource constrained public health system with outcomes similar to private sector. Abstract : This study reports our 10‐year experience from a high volume public bariatric service which delivers multi‐disciplinary care for primary and revisional procedures with mid‐ to long‐term follow‐up. This study confirms that bariatric surgery in Australia can be delivered effectively in resource constrained public health system with outcomes similar to private sector.